The paradox - Fletcher, Charlie, 1960- (Fletcher, Charlie, 1960- Oversight Trilogy, 2015)
"The Last Hand of the Oversight still patrols the border between the natural and supernatural, holding a candle to the darkness. But this new Hand is unproven, its fresh members untrained, its veterans weary and battle-scarred. Their vulnerability brings new enemies into the city, and surprising new allies from across the sea. But most surprising of all are new revelations about the Oversight's past, revelations that will expose the true peril of the world in which Sharp and Sara are trapped -- the secret of the Black Mirrors, and what lies beyond. And the catastrophic danger that will follow them home, if they ever manage to return. The dark waters rise. The candles are guttering. But the light still remains. For now..."--provided from Amazon.com.